Effects of Sex and Gender on Adaptation to Space: Cardiovascular Alterations - Platts, Steven H. (J Womens Health (Larchmt), 2014)
Sex and gender differences in the cardiovascular adaptation to spaceflight were examined with the goal of optimizing the health and safety of male and female astronauts at the forefront of space exploration. Female astronauts are more susceptible to orthostatic intolerance after space flight; the visual impairment intracranial pressure syndrome predominates slightly in males. Since spaceflight simulates vascular aging, sex-specific effects on vascular endothelium and thrombotic risk warrant examination as predisposing factors to atherosclerosis, important as the current cohort of astronauts ages. Currently, 20% of astronauts are women, and the recently selected astronaut recruits are 50% women. Thus there should be expectation that future research will reflect the composition of the overall population to determine potential benefits or risks. This should apply both to clinical studies and to basic science research.